Pengaruh Kepuasan Kerja Terhadap Keterikatan Kerja pada Karyawan Rumah Sakit - Herio Rizki Dewinda; Djamaludin Ancok; Nilam Widyarini (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
This study aims to examine the effect of job satisfaction on work engagement in hospital employees. The study sample was taken from permanent employees at the SP Hospital in West Sumatra with a total number of subjects as many as 285 people, sampling was done by proportionate stratified random sampling technique. The measuring instrument used is the result of an adaptation of a pre-existing measuring instrument by changing the measuring instrument to Indonesian. Work engagement is measured using the Utrecht Work Engagement Scale (UWES), while job satisfaction is measured using the Minnesota Satisfaction Questionnaire. Based on the results of data analysis conducted, the hypothesis was accepted, there was a significant effect between job satisfaction on work engagement in hospital employees, as indicated by the t-value of 10.681 with a significance of 0.000 (p <0.05). The contribution of job satisfaction to work engagement is 28.7% and the rest is influenced by other variables.